Pharmacokinetics and Pharmacodynamics of Cinacalcet in Hepatic Impairment: Phase I, Open-Label, Parallel-Group, Single-Dose, Single-Centre Study - Padhi, Desmond; Harris, Robert Z.; Salfi, Margaret; Noveck, Robert J.; Sullivan, John T. (Clinical drug investigation, 2008)
Background and objective: The calcimimetic cinacalcet lowers blood parathyroid hormone (PTH), calcium and phosphorus levels and calcium-phosphorus product in patients with chronic kidney disease receiving dialysis. Cinacalcet is metabolized primarily through oxidative and conjugative pathways. Hepatic disease has the potential to alter cinacalcet metabolism. Thus, it is important to establish the potential for altered cinacalcet metabolism according to the level of hepatic function. This study aimed to evaluate the pharmacokinetics and pharmacodynamics of cinacalcet in subjects with different degrees of hepatic function. Methods: This was a phase I, open-label, single-dose, parallel-group, single-centre study that included 24 subjects (six with normal hepatic function and six each with mild, moderate and severe hepatic impairment according to Child-Pugh criteria). Subjects were given a single 50 mg oral dose of cinacalcet. Blood samples were taken for pharmacokinetic (pre-dose and up to 120 hours post-dose) and pharmacodynamic (pre-dose and up to 72 hours post-dose) evaluations. Plasma concentrations of cinacalcet were determined using a validated normal phase turbo ion spray liquid chromatography-mass spectrometry/mass spectrometry assay. Serum ionized calcium levels were determined by standard biochemical measures, and PTH levels were determined using an immunometric intact PTH (iPTH) assay. The primary endpoints of the study were area under the concentration-time curve from 0 to time t (AUC t ), AUC from 0 to infinity (AUC ∞ ) and maximum plasma concentration (C max ). Other pharmacokinetic parameters (time to C max [t max ], terminal half-life [t1/2β], total body clearance [CL/F] and protein binding) and the effect of cinacalcet on plasma PTH and serum calcium were secondary endpoints. Results: Total cinacalcet exposure (AUC ∞ ) was comparable in subjects with normal hepatic function and mild hepatic impairment. In subjects with moderate and severe hepatic impairment, mean AUC ∞ was 2.4- and 4.2-fold higher, respectively, than in healthy subjects. Cinacalcet t1/2β was 1.3- and 1.7-fold longer in subjects with moderate and severe hepatic impairment, respectively, compared with subjects with normal hepatic function. Mean C max and t max , as well as protein binding, were similar in all groups. Consistent with the increase in cinacalcet exposure, decreases in iPTH tended to be greater and prolonged in subjects with moderate and severe hepatic impairment. In this study, cinacalcet was well tolerated. Conclusion: These data demonstrate that cinacalcet can be used without dose adjustment in patients with mild hepatic impairment. However, increased drug exposure observed in subjects with moderate to severe hepatic impairment indicates that iPTH and serum calcium levels should be monitored closely and physicians should be more cautious about dose titration in patients with moderate or severe hepatic impairment.